Exploring Potentials and Challenges to Develop Twenty-First Century Skills and Computational Thinking in K-12 Maker Education - Iwata, Megumi; Pitkänen, Kati; Laru, Jari; Mäkitalo, Kati (Frontiers in Education, 2020)
Interests in Maker Education have been increasing among K-12 educators. In this study, we focused on one of the contexts of Maker Education, digital fabrication activities, at a makerspace in Finland. We aimed to explore: 1) the potentials and the factors to develop twenty-first century skills and computational thinking practices through digital fabrication activities, and 2) challenges of utilizing digital fabrication in K-12 Maker Education. We examined perspectives of teachers and facilitators who have roles to support pupils in Maker Education. We presented three cases of school visits (3-5 days), where the pupils (7th-9th grades) created tangible artefacts with digital fabrication facilities at the makerspace. We collected data through participants’ observation, informal interviews and focus group interviews with teachers and facilitators. For data analysis, we employed theory-driven and data-driven approaches. The results showed that digital fabrication activities can provide learning opportunities for twenty-first century skills and computational thinking practices. The teachers and the facilitators discussed the six factors of digital fabrication activities which influenced pupils’ learning. However, the result also indicated the possibility that the teachers and the facilitators might not be familiar with the concepts of computational thinking. Also, different perspectives between the teachers and the facilitators towards the structure of the current activities surfaced. By identifying potentials and challenges of the current practices, the study has implications to advance Maker Education to be better integrated into K-12 school contexts.